Simple and efficient optical fiber recoating procedure - F.A.C. Nobrega; E.A.W. Menezes; R. Reichenbächer; C. Scheffler; R.F. Abreu; E.F. Morais; C.M.B. Cordeiro; A. Spickenheuer; S.C. Amico; A.S.B. Sombra (Materials Letters: X, 2025)
This article describes a rapid method of recoating optical fibers employing the dip-coating technique, using a polypropylene film former with a silane coupling agent, which reacts, yielding a protective film over the core. The silica optical fibers were recoated with film former sizings at concentrations of 5 % and 10 %. Microscopic analysis of the recoated area showed a smooth surface and an increase in diameter of 13.4 % and 16.5 %, respectively, compared to the uncoated fiber. The maximum curvature radius of the uncoated fibers was 3.69 ± 1.70 mm, whereas the fibers recoated with the 5 % and 10 % film former sizings reached a bending radius of 1.71 ± 1.38 mm and 1.55 ± 0.98 mm, representing 53.9 % and 57.9 % reduction, respectively. This shows that recoated optical fibers are more flexible than the uncoated ones. In all, the recoating of optical fibers proposed in this work results in fibers with smooth and flexible surfaces using a simple, cost-effective technique that can be implemented on large-scale processes.